Seizing opportunities: Object neophobia as a factor mediating technical innovation in Goffin´s cockatoos? - Theresa Rössler; Mark O’Hara; Berenika Mioduszewska; Remco Folkertsma; Roger Mundry; Alice M. I. Auersperg (PLoS ONE, 2025)
Most studies find substantial inter-individual differences in problem-solving performance within a species, which can drastically influence an individual´s fitness. It has been suggested that innovative behavior can be strongly affected by behavioral traits, such as exploration, persistence, neophilia, and neophobia. Individuals who are more neophobic than others may encounter fewer opportunities or favorable interactions but may also show differences in cognitive ability. We tested eleven captive Goffin’s cockatoos ( Cacatua goffiniana ), a model species for innovative problem-solving, for individual variation in object neophobia and whether it relates to motivation and performance in a problem-solving task. We found no evidence that the less neophobic cockatoos were generally better problem-solvers, nor that they were more eager to engage with the setup after familiarization. Our results suggest that object neophobia in this group of Goffin’s cockatoos may not be directly linked to either the ability to innovate or the general motivation to interact with experimental apparatuses. We discuss what these findings could imply for the emergence of innovative behavior as well as the potential limitations of individually tested animals of a highly social species.